BIAYA SENDIRI DAN FAKTOR PENENTU KESULITAN EKONOMI PADA PASIEN PENYAKIT GINJAL KRONIK DENGAN HEMODIALISIS DI RUMAH SAKIT UMUM KABUPATEN TANGERANG PERIODE OKTOBER–DESEMBER 2018 - Syari, Delviza; Sarnianto, Prih; R, Hesti Utami (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2019)
ABSTRACTChronic Kidney Disease (CKD) is a global public health problem with increasing prevalence and incidence, poor prognosis and high costs. The prevalence of CKD increases with the increasing number of elderly people and the incidence of diabetes mellitus (DM) and hypertension. In Indonesia, the treatment of kidney diseases is the second largest financing of the Health Social Security Organizing Agency (BPJS-K) after heart disease. In addition to the cost of hemodialysis, indirect costs or own costs or costs according to the patient's perspective (out of pocket, OOP) must be borne with the patient. OOP costs can absorb most household resources and have an impact on poverty. Analitical descriptive research with cross sectional method is intended to find out determine the own costs incurred by patients and the factors that cause economic difficulties. Primary data was taken through interviews with a structured questionnaire for 74 people with CKD who underwent hemodialysis therapy for more than one year at the Tangerang District General Hospital Tangerang in October-December 2018. Own costs that incurred by the family of patients are calculated in accounting determinant of economic difficulties were analyzed by logistic regression tests using appropriate software. The costs that spent by (families) CKD patients at General Hospital include transportation costs including parking (average Rp 528.000), consumption (Rp 413.625), purchase of drugs and supplements that are not covered (Rp 315.319), costs of caregiver (Rp 650.000) and decreased in productivity (Rp 878,112). Patients affected economic difficulties is 50 people (67,6%). In addition to OOP, the factors that significantly influence the economic difficulties (family) of patients are income. Patients who have the potential to experience economic difficulties are those who earn Rp>4.000.000 (p = 0,020; OR = 0.253), will experience economic difficulties 3,95 times less than patients with odds income of Rp<2.000.000 and Rp2.000.000-4.000.000. Economic difficulties are illustrated by the inability of patients to pay home installments/house rent, electricity, telephone, water bills, drug purchases and pay for children's education. Also, economic difficulties can be shown from the situation after patients doing hemodialysis, moving house, using savings that should be for other purposes, asking for financial assistance from friends, borrowing money with personal guarantees, selling assets or other assets, and implementing other strategies to continue to finance life. Keywords: chronic kidney failure (CRF), out of pocket (OOP), economic difficulties, hemodialysisABSTRAK Penyakit ginjal kronik (PGK) merupakan masalah kesehatan masyarakat global dengan prevalensi dan insiden yang terus meningkat, prognosis yang buruk dan biaya yang tinggi. Selain besarnya biaya hemodialisis, biaya tidak langsung atau biaya sendiri atau biaya menurut perspektif pasien (out of pocket, OOP) harus ditanggung pasien. Adanya pengeluaran biaya OOP dapat menyerap sebagian besar sumber daya rumah tangga dan berdampak pada kemiskinan. Penelitian deskriptif analitik dengan metode cross sectional ini bertujuan untuk mengetahui biaya sendiri yang dikeluarkan oleh pasien serta faktor-faktor yang menyebabkan terjadinya kesulitan ekonomi. Data primer diambil melalui wawancara dengan kuesioner terstruktur terhadap 74 orang pasien PGK yang menjalani terapi hemodialisis lebih dari satu tahun di RSU Kabupaten Tangerang pada Oktober–Desember 2018. Biaya sendiri yang dikeluarkan oleh pasien dihitung secara akuntansi dan faktor penentu kesulitan ekonomi dianalisis dengan uji regresi logistik menggunakan perangkat lunak yang sesuai. Biaya sendiri yang dikeluarkan oleh (keluarga) pasien PGK di RSU Kabupaten Tangerang meliputi biaya transportasi termasuk parkir (rata-rata Rp 528.000), makan dan minum (Rp 413.625), pembelian sendiri obat dan suplemen (Rp 315.319), biaya untuk pendamping (Rp 650.000) dan penurunan produktivitas (Rp 878,112). Pasien yang mengalami kesulitan ekonomi berjumlah 50 orang (67,6%). Selain biaya sendiri, faktor yang berpengaruh secara signifikan terhadap kesulitan ekonomi (keluarga) pasien adalah penghasilan. Pasien yang berpotensi mengalami kesulitan ekonomi adalah yang berpenghasilan Rp>4.000.000 (p = 0,020; OR = 0,253) akan mengalami kesulitan ekonomi 3,95 kali lebih kecil dibandingkan pasien dengan penghasilan Rp<2.000.000 dan Rp2.000.000-4.000.000. Kesulitan ekonomi yang dialami pasien hemodialisis berupa keadaan keadaan ekonomi/keuangan pasien yang pas-pasan/miskin. Kesulitan ekonomi digambarkan dengan ketidakmampuan pasien membayar cicilan rumah/uang sewa rumah, tagihan listrik, telepon, air, pembelian obat dan membayar pendidikan anak. Kesulitan ekonomi juga dapat dilihat dari keadaan setelah pasien menjalani hemodialisis yaitu mengalami pindah rumah, menggunakan tabungan yang seharusnya untuk keperluan lain, meminta bantuan keuangan dari kerabat, pinjam uang dengan jaminan pribadi, jual asset atau harta lainnya serta melakukan strategi lain agar dapat terus membiayai hidup. Kata Kunci: penyakit ginjal kronik (pgk), biaya sendiri, kesulitan ekonomi, hemodialisis